STUDIES ON THE ACTIVITY AND DAILY EXODUS OF ROUSETTEUS LECHENAULTI A CAVE DWELLING BAT IN TWO GEOGRAPHICALLY ISOLATED CAVES OF ORISSA, INDIA - SRIANGA TILAK PATNAIK; B. C. GURU; P. K. MOHANTY; C. S. K. MISHRA (The Bioscan, 2010)
Approximately 330 cave dwelling bats of Udayagiri cave in Bhubaneswar and 170 bats of Ganesh cave, Hinjilikatu in Orissa, India were observed during four different season’s spring, summer, Autumn and Winter. The longest pre emergence activity was recorded on June 21, 2009 for Ganesh cave and on June 22, 2009 for Udayagiri cave. The shortest pre emergence activity was recorded on December 20, 2009 for Ganesh cave and on December, 21, 2009 for Udayagiri cave. Significant correlation (p<0.05) was observed between the pre emergence activity and length of the day during all the seasons of study. The intensity of the emergence activity increased sharply and then declined slowly in both the caves. Statistically significant correlation (p<0.05) was observed between the timing of emergence of first bat and the time of sunset in both the caves. The timing of end activity (the time when the last bat returned) precisely preceded the timing of sunrise (of next day) irrespective of the month of study. A statistically significant correlation (p<0.05) was observed between the timing of return of the last bat and the time of sunset. Diurnal rhythm in the activity patterns of the bat colonies were greatly influenced by natural light- dark cycle, temperature and availability of food.